Drug misuse by teenagers in schools in Benin and genetic polymorphism of cytochrome p450: interest and perspectives of cytochrome p450 genotyping - Agbanlinsou, Arnaud Coffi; Cisse, Ibrahim; Laleye, Anatole (International Journal Of Community Medicine And Public Health, 2022)
The misuse of psychoactive substances by students is a reality in Beninese schools. These students are exposed to experimentation with these substances with or without prescriptions. The systematic genotyping of cytochromes in these students and in general in subjects exposed to the use of psychoactive substances would be an asset in their therapeutic management and more specifically in the adaptation of dosages and will also allow us to add a particular touch during sensitizations on the experimentation of substances. To achieve this, we checked the availability of drugs that metabolize by cytochromes 2D6 and 3A4 and that are in pharmacies in Benin. What would happen when they consume one or more substances that are metabolized by two cytochrome? PharmGKB is a pharmacogenomics knowledge base that provides information on how human genetic variation affects drug response by collecting information on clinically relevant gene-drug associations and genotype-phenotype relationships. For dosage individualization in therapeutics, the use of the PharmGKB knowledge base preceded by cytochrome genotyping in exposed subjects are assets that clinicians should make use of today for disease treatment.